Widowhood, widowhood duration, and loneliness among older adults in China. (August 2021) - Yang, Fang; Gu, Danan
Abstract: Background: Widowhood is a distressful life event that is associated with loneliness in older adults. However, widowhood is not a binary event, and little is known about the role of widowhood duration in loneliness and about the relationship between widowhood duration and loneliness in different age and sex groups. Given the increases in aging population and in widowed older adults in China, we examined whether and how widowhood and widowhood duration were associated with loneliness in different age and sex groups among Chinese older adults. Methods: Five waves of Chinese Longitudinal Healthy Longevity Survey 2002–2014 were used. The analysis included 34, 440 sampled individuals aged 65 and above. Random intercept ordered logistic models were used to examine relations between widowhood, its duration and loneliness in the entire sample and by age and sex groups. Results: Results show that with a wide set of covariates controlled for, widowhood was a significant correlate of loneliness in older adults (OR = 2.34, p  < .001); and those who were remarried after widowhood were less likely to be lonely compared to their not-remarried counterparts (OR = 0.47, p  < .001). In addition, widowhood was associated with more than twice greater odds of loneliness in the first couple of years following bereavement of spouse (OR = 3.09, p < .001) compared to the currently married older adults. The increased odds ratio of loneliness slightly decreased with the length of widowhood, but it was still significant, even after 40 years of bereavement (OR = 1.96, p < .001). Conclusions: These findings are mostly consistent across age and sex groups. In conclusion, this study sheds light on the relationship between widowhood duration and loneliness and the role of remarriage in widowed older adults' loneliness based on a nationwide survey in China. Widowhood has an acute and long-lasting effect on loneliness in older adults. Remarriage after widowhood could largely reduce or offset the risk of loneliness. Highlights: Widowhood was significantly correlated with loneliness in Chinese older adults. The widowhood-loneliness link varied across age groups and gender. The effects of widowhood on loneliness decreased with age. Widowhood effect on loneliness was acute and long-lasting. Remarriage after widowhood diminishes risk of loneliness.